Clinical Outcomes for Peripartum Cardiomyopathy in North America: Results of the IPAC Study (Investigations of Pregnancy-Associated Cardiomyopathy) - McNamara, Dennis M; Elkayam, Uri; Alharethi, Rami; Damp, Julie; Hsich, Eileen; Ewald, Gregory; Modi, Kalgi; Alexis, Jeffrey D; Ramani, Gautam V; Semigran, Marc J; Haythe, Jennifer; Markham, David W; et al. (Journal of the American College of Cardiology, 2015)
Peripartum cardiomyopathy (PPCM) remains a major cause of maternal morbidity and mortality. This study sought to prospectively evaluate recovery of the left ventricular ejection fraction (LVEF) and clinical outcomes in the multicenter IPAC (Investigations of Pregnancy Associated Cardiomyopathy) study. We enrolled and followed 100 women with PPCM through 1 year post-partum. The LVEF was assessed by echocardiography at baseline and at 2, 6, and 12 months post-partum. Survival free from major cardiovascular events (death, transplantation, or left ventricular [LV] assist device) was determined. Predictors of outcome, particularly race, parameters of LV dysfunction (LVEF), and remodeling (left ventricular end-diastolic diameter [LVEDD]) at presentation, were assessed by univariate and multivariate analyses. The cohort was 30% black, 65% white, 5% other; the mean patient age was 30 ± 6 years; and 88% were receiving beta-blockers and 81% angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. The LVEF at study entry was 0.35 ± 0.10, 0.51 ± 0.11 at 6 months, and 0.53 ± 0.10 at 12 months. By 1 year, 13% had experienced major events or had persistent severe cardiomyopathy with an LVEF <0.35, and 72% achieved an LVEF ≥0.50. An initial LVEF <0.30 (p = 0.001), an LVEDD ≥6.0 cm (p < 0.001), black race (p = 0.001), and presentation after 6 weeks post-partum (p = 0.02) were associated with a lower LVEF at 12 months. No subjects with both a baseline LVEF <0.30 and an LVEDD ≥6.0 cm recovered by 1 year post-partum, whereas 91% with both a baseline LVEF ≥0.30 and an LVEDD <6.0 cm recovered (p < 0.00001). In a prospective cohort with PPCM, most women recovered; however, 13% had major events or persistent severe cardiomyopathy. Black women had more LV dysfunction at presentation and at 6 and 12 months post-partum. Severe LV dysfunction and greater remodeling at study entry were associated with less recovery. (Investigations of Pregnancy Associated Cardiomyopathy [IPAC]; NCT01085955).